Analysis of the Screening Results for Congenital Adrenal Hyperplasia Involving 7.85 Million Newborns in China: A Systematic Review and Meta-Analysis - Li, Zhuoguang; Huang, Lianjing; Du, Caiqi; Zhang, Cai; Zhang, Mini; Liang, Yan; Luo, Xiaoping (Frontiers in Endocrinology, 2021)
Background：Congenital adrenal hyperplasia (CAH) is a group of congenital genetic diseases caused by defective steroidogenesis. Our study aims to systematically analyze the screening results for CAH in Chinese newborns. Methods：Studies were searched from PubMed, Web of Science, Cochrane library and some Chinese databases up to September, 2020. Meta-analysis was performed after quality assessment and data extraction. Results：After a review of 2 694 articles, we included 41 studies enrolling 7 853 756 newborns. In our study, we found that the incidence of CAH in China was 0.43‱ [95% confidence intervals(CI), (0.39‱, 0.48‱)], or 1/23 024 [95%CI, (1/25 757,1/20 815)]. 27 studies were included for analysis of the screening positive rate, which gave a rate of 0.66% [95%CI, (0.54%, 0.78%)]. As for the recall rate of positive cases, 17 studies were included and showed that the recall rate reached 86.17% [95%CI, (82.70%, 89.64%)]. Among the CAH patients, the ratio of males to females was 1.92:1 (119:62), and the ratio of salt wasting (SW) to simple virilization (SV) type was 3.25:1 (104:32). The average 17-hydroxyprogesterone (17-OHP) value of CAH was 393.40 ± 291.85 nmol/L (Range 33-1 300 nmol/L); there was no significant difference between male and female patients (437.17 ± 297.27 nmol/L v.s. 322.25 ± 293.04 nmol/L, P=0.16), but a significant difference was found between SW and SV patients (483.29 ± 330.07 nmol/L v.s. 73.80 ± 7.83nmol/L, P=0.04). Conclusion：We systematically analyzed the current situation of neonatal CAH screening in China, which will deepen our understanding for future CAH screening and early diagnosis.